Cell Adhesion Molecules as Modulators of the Epidermal Growth Factor Receptor - Irina Kozlova; Vladimir Sytnyk (Cells, 2024)
Cell adhesion molecules (CAMs) are cell surface glycoproteins mediating interactions of cells with other cells and the extracellular matrix. By mediating the adhesion and modulating activity of other plasma membrane proteins, CAMs are involved in regulating a multitude of cellular processes, including growth, proliferation, migration, and survival of cells. In this review, we present evidence showing that various CAMs interact with the epidermal growth factor receptor (EGFR), a receptor tyrosine kinase inducing pro-proliferative and anti-apoptotic intracellular signaling in response to binding to several soluble ligands, including the epidermal growth factor. We discuss that CAMs are involved in regulating EGFR signaling by either potentiating or inhibiting the soluble ligand-dependent activation of EGFR. In addition, CAMs induce soluble ligand-independent forms of EGFR activity and regulate the levels of EGFR and its ligand-induced degradation. The CAM-dependent modulation of EGFR activity plays a key role in regulating the growth, proliferation, and survival of cells. Future research is needed to determine whether these processes can be targeted in both normal and cancerous cells by regulating interactions of EGFR with various CAMs.